(untitled) (REMUNOM, 2024)
Schizophrenia is one of the most prevalent psychiatric disorders worldwide. It affects approximately 1% of the world population, accounting for 25% of international psychiatric illnesses. Its clinical course is heterogeneous, with around 20% to 30% of the patients presented presenting some type of complete recovery, 30% being in remission with special loss of functionality and 30% with significant and persistent impact on the professional, social and emotional spheres. . Refractory schizophrenia, or popularly known as resistant schizophrenia, affects around 30% of observed patients and is characterized by the persistence of positive symptoms, such as hallucinations and delusions. In these cases, clozapine is the antipsychotic of choice. The research seeks to deepen the understanding in detail about the impacts of refractory schizophrenia and the effectiveness of available treatments, in addition to other available alternatives, offering support for effective therapeutic strategies.